Faktor-Faktor yang Mempengaruhi Pendapatan Keluarga Miskin di Kecamatan Panarukan Kabupaten Situbondo - Radhitia Brianjaya; I. Wayan Subagiarta; Z. Zainuri (e-Journal Ekonomi Bisnis dan Akuntansi, 2018)
The purpose of this study was to determine the effect of education, number of the family work participation, age and type of work to the poor family income in Panarukan Situbondo district. This research population is 3.118 poor families in Panarukan Situbondo district. Then sampled by stratified random sampling with 97 people. The method used in this research is Ordinary Least Square. Based on the research result, the result thatresearch, the number of work participation, age and type of work affect the income of poor family in the district of Situbondo Panarukan. the result that education, the number of work participation, age and type of work affect the income of poor family in Panarukan Situbondo district. It can be concluded the independent variables simultaneously affect the dependent variable. variable means of education, the number of work participation and the type of work has a positive and significant effect, while age has a negative effect and insignificant.Keywords : Education, work participation, age and type of work